Genetics of Paroxysmal Dyskinesia: Novel Variants Corroborate the Role of KCNA1 in Paroxysmal Dyskinesia and Highlight the Diverse Phenotypic Spectrum of KCNA1- and SLC2A1-Related Disorders - Kegele, Josua; Krüger, Johanna; Koko, Mahmoud; Lange, Lara; Marco Hernandez, Ana Victoria; Martinez, Francisco; Münchau, Alexander; Lerche, Holger; Lauxmann, Stephan (Frontiers in Neurology, 2021)
Paroxysmal dyskinesias (PxD) are rare movement disorders with characteristic episodes of involuntary mixed hyperkinetic movements. Scientific efforts and technical advances in molecular genetics have led to the discovery of a variety of genes associated with PxD, however clinical and genetic information of rarely affected genes or infrequent variants is often limited. In our case series, we present two individuals with PxD including one with classical paroxysmal kinesiogenic dyskinesia, who carry new likely pathogenic de novo variants in KCNA1 (p.Gly396Val and p.Gly396Arg). The gene has only recently been discovered to be causative for familial paroxysmal kinesiogenic dyskinesia. We also provide genetic evidence for pathogenicity of two newly identified disease-causing variants in SLC2A1 (p.Met96Thr and p.Leu231Pro) leading to paroxysmal exercise-induced dyskinesia. Since clinical information of carriers of variants in known disease-causing genes is often scarce, we encourage to share clinical data of individuals with rare or novel (likely) pathogenic variants to improve disease understanding.